Green synthesis and third-order nonlinear optical properties of 6-(9H-carbazol-9-yl) hexyl acetate. (14th October 2016) - Chen, Baili; Geng, Feng; Luo, Xuan; Zhong, Quanjie; Zhang, Qingjun; Fang, Yu; Huang, Chuanqun; Yang, Ruizhuang; Shao, Ting; Chen, Shufan
Abstract: An extremely simple and green approach for the synthesis of photoelectric material 6-(9H-carbazol-9-yl) hexy-acetate (CHA) has been described in detail. The molecular structure of CHA was identified with Fourier transform infrared (FT-IR) spectra and 1 H Nuclear Magnetic Resonance ( 1 H NMR) spectroscopy. The optical absorption of CHA was recorded using ultraviolet-visible (UV–vis) spectrum. Notably, the reaction was accomplished in water medium instead of traditional toxic solvents (e.g., benzene and chloroform). The yield of CHA is up to 99%, which is increased by 13% compared with the traditional method. The approach developed by us makes it possible to achieve commercial production of CHA. Moreover, the thermal stability of CHA was studied with thermogravimetric (TG) and derivative thermogravimetric (DTG) method. The third-order nonlinear optical (NLO) properties of CHAn (obtained by new method) and CHAt (obtained by traditional method) have been studied by a Z-scan technique at 440 nm. The thermal decomposition temperature is above 200 °C. The third-order NLO of CHAn and CHAt are the same. The third-order NLO susceptibility χ (3) and two photon Figures of Merit (FOMs) of CHA are 1.58 × 10 −8 (esu) and 4.55, respectively. The results reveal that CHA may be a promising candidate for all-optical switching application.